Ongka's big moka [videorecording] ([S.l.] Shanachie Entertainment Corp., 1994)
Ongka, tribal leader of the Kawelka tribe of highland New Guinea; spent five years using his kill as an orator and negotiator to amess pigs and assorted other valuables which he will give away in a festive ceremony, amoka.
VHS.
Keywords: Ongka; Kawelka (New Guinea people)